Free fetal DNA – Clinical applications in prenatal diagnosis. - Guzmán, Luis (2015)
Free fetal DNA (ffDNA) was discovered over a decade ago and since research has been focused in discovering its origin, how the mother metabolizes it and how to use the information that it contains for clinical diagnosis. Some of these questions have been answered; however, more research is needed. Currently, clinical applications include use of ffDNA as a tool in sex determination of the baby during the first trimester, in the prediction of future pregnancy complications, and in the diagnosis of monogenic diseases. The aim of this article is to provide an overview of current ffDNA applications in prenatal genetic diagnosis.